Evaluation of ground‐based black carbon measurements by filter‐based photometers at two Arctic sites. Issue 6 (29th March 2017) - Sinha, P. R.; Kondo, Y.; Koike, M.; Ogren, J. A.; Jefferson, A.; Barrett, T. E.; Sheesley, R. J.; Ohata, S.; Moteki, N.; Coe, H.; Liu, D.; Irwin, M.; et al.
Abstract: Long‐term measurements of the light absorption coefficient ( b abs ) obtained with a particle soot absorption photometer (PSAP), b abs (PSAP), have been previously reported for Barrow, Alaska, and Ny‐Ålesund, Spitsbergen, in the Arctic. However, the effects on b abs of other aerosol chemical species coexisting with black carbon (BC) have not been critically evaluated. Furthermore, different mass absorption cross section (MAC) values have been used to convert b abs to BC mass concentration ( M BC = b abs /MAC). We used a continuous soot monitoring system (COSMOS), which uses a heated inlet to remove volatile aerosol compounds, to measure b abs ( b abs (COSMOS)) at these sites during 2012–2015. Field measurements and laboratory experiments have suggested that b abs (COSMOS) is affected by about 9% on average by sea‐salt aerosols. M BC values derived by COSMOS ( M BC (COSMOS)) using a MAC value obtained by our previous studies agreed to within 9% with elemental carbon concentrations at Barrow measured over 11 months. b abs (PSAP) was higher than b abs (COSMOS), by 22% at Barrow (PM1 ) and by 43% at Ny‐Ålesund (PM10 ), presumably due to the contribution of volatile aerosol species to b abs (PSAP). Using b abs (COSMOS) as a reference, we derived M BC (PSAP) from b abs (PSAP) measured since 1998. We also established the seasonal variations of M BC at these sites. Seasonally averaged M BC (PSAP) decreased at a rate of about 0.55 ± 0.30 ng m −3 yr −1 . We also compared M BC (COSMOS) and scaled M BC (PSAP) values with previously reported data and evaluated the degree of inconsistency in the previous data. Key Points: We evaluated the accuracy of black carbon (BC) measurements at Barrow, Alaska, and Ny‐Ålesund, Spitsbergen, in the Arctic At Barrow, seasonally averaged BC mass concentrations decreased in winter and summer at a rate of 0.55 ± 0.30 ng m −3 yr −1 during 1998–2015 We established seasonal variations of BC at the two sites and evaluated the causes of the inconsistency of the previously reported data